The inorganic polymer, polyphosphate, blocks binding of SARS-CoV-2 spike protein to ACE2 receptor at physiological concentrations - Neufurth, Meik (Biochem Pharmacol, 2020)
Inorganic polyphosphate (polyP) is a morphogenetically active and metabolic energy-delivering physiological polymer that is released from blood platelets. Here, we show that polyP efficiently inhibits the binding of the envelope spike (S)-protein of the coronavirus SARS-CoV-2, the causative agent of COVID-19, to its host cell receptor ACE2 (angiotensin-converting enzyme 2). To stabilize polyP against the polyP-degrading alkaline phosphatase, the soluble polymer was encapsulated in silica/polyP nanoparticles. Applying a binding assay, soluble Na-polyP (sizes of 40 P(i) and of 3 P(i) units) as well as silica-nanoparticle-associated polyP significantly inhibit the interaction of the S-protein with ACE2 at a concentration of 1 µg/mL, close to the level present in blood. This inhibition is attributed to an interaction of polyP with a basic amino acid stretch on the surface of the receptor binding domain of S-protein. PolyP retains its activity in a flushing solution, opening a new strategy for the prevention and treatment of SARS-CoV-2 infection in the oropharyngeal cavity. The data suggest that supplementation of polyP might contribute to a strengthening of the human innate immunity system in compromised, thrombocytopenic COVID-19 patients.